Environmental awareness and humanities for environmental sustainability in the 21st century: rethinking development through social science lenses in the nordic nations - Wang, Chaoyang; Zhu, Linjiang; Zhang, Xiaojuan (Frontiers in Environmental Science, 2026)
Despite their reputation as global front-runners in environmental governance and institutional excellence, the Nordic countries are increasingly grappling with complex sustainability pressures—from rapid urbanization and cultural realignments to evolving educational landscapes and shifting socio-economic dynamics. This study explores the impact of economic growth (EG), urbanization (URB), humanities investment (HUM), social trust (SS), and environmental awareness potential (EAP) on environmental sustainability (ES), measured via biocapacity per capita. Using panel data from 2002 to 2023 across five Nordic nations, the analysis applies the Method of Moments Quantile Regression (MMQR) and Feasible Generalized Least Squares (FGLS) to capture heterogeneous effects and ensure robustness. The results show that HUM consistently enhances ES, EG contributes positively at higher sustainability levels, while URB increasingly undermines ES in more advanced contexts. SS has a persistent negative effect, and EAP exhibits a nonlinear U-shaped relationship—initially reducing ES before improving it after a threshold. This study makes a novel empirical contribution by systematically integrating educational and cultural dimensions—often treated as peripheral in sustainability modeling—into a rigorous econometric framework. Specifically, it operationalizes humanities investment and environmental awareness as core explanatory factors within a panel structure, addressing critical gaps in the literature that have historically prioritized economic and technological determinants. By doing so, the research advances an interdisciplinary understanding of sustainability transitions as culturally embedded and socially mediated processes. Findings offer actionable insights for policymakers, particularly in aligning environmental education, cultural investment, and urban planning with the Sustainable Development Goals (SDGs), to drive sustainable transitions in the 21st century.